Tensions in the political-administrative system: Experiences from Norway - Kolltveit, Kristoffer (Politica, 2016)
The Bo Smith report suggests various changes to make the Danish political-administrative system better adapted to new demands in society. In this article, several of these changes are considered in light of experience from Norway. Denmark and Norway share a common heritage, but their systems have developed somewhat differently, not least when it comes to the number and function of political appointees in ministries. The article first describes the political-administrative system in Norway before considering the various proposals. The Bo Smith report does not suggest introducing more political appointees in Danish ministries. The article argues, however, that a strengthening of the political layer together with written guidelines might make it easier for civil servants to act party politically neutral.